2000
DOI: 10.1076/0271-3683(200004)2041-5ft313
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of enzymes of arginine metabolism in the rat eye

Abstract: These results indicate that arginine recycling activity from citrulline is present widely in ocular tissues, whereas expression of arginase II differs among the tissues. We suggest that NO production may be regulated by these enzymes in the cells where NO synthase is colocalized. Colocalization of arginase II and ornithine aminotransferase suggests a role for arginase II in collagen synthesis in the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although the exact ornithine metabolism in the eye is obscure, it seems to differ from that in the liver; proline oxidase and ornithine transcarbamylase are negligible in the eye (90,91) . Ornithine in the retina may be metabolised into proline by the cooperative action of OAT and pyrroline-5-carboxylate reductase and into putrescine by the action of ornithine decarboxylase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact ornithine metabolism in the eye is obscure, it seems to differ from that in the liver; proline oxidase and ornithine transcarbamylase are negligible in the eye (90,91) . Ornithine in the retina may be metabolised into proline by the cooperative action of OAT and pyrroline-5-carboxylate reductase and into putrescine by the action of ornithine decarboxylase.…”
Section: Discussionmentioning
confidence: 99%
“…Among bovine ocular tissues, arginase activity was high in the retina and uvea; pyrroline-5-carboxylate reductase activity was high in the lens, cornea and retina; pyrroline-5-carboxylate dehydrogenase activity was high in the uvea but low in the retina; and proline oxidase activity was negligible in all ocular tissues (90) . Koshiyama et al (91) reported that mRNA for ornithine transcarbamylase analysed by RT-PCR was not detected in the rat ocular tissues and that arginase II (nonhepatic-type) mRNA was detected in the retina and weakly in the cornea, whereas arginase I (hepatic-type) mRNA was not detected in rat eyes. Thus, the exact ornithine metabolism in the eye, particularly in the RPE, is unknown.…”
Section: Ornithine Metabolism In the Eyementioning
confidence: 99%
“…In contrast, arginine levels were dramatically increased in Müller cells following GS inhibition. Given that the brain and retina do not have a urea cycle and remove excess nitrogen via GS amidation of glutamate (Koshiyama et al. 2000; Wiesinger 2001), the likely explanation is a ‘flow back’ effect secondary to altered glutamate catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Argininosuccinate is the precursor of arginine which at the same time leads to urea in the urea cycle. This enzyme was detected in the eyes of rats as well as in other tissues [21], demonstrating its ubiquity and giving rise to the belief that its expression is dependent on the tissue needs (not like in the liver where it is continuously expressed). Koshiyama et al (2000) also showed that arginine recycling activity from citrulline was present in ocular tissues [21].…”
Section: Metabolomic Study With Patients With High and Low Myopiamentioning
confidence: 95%